Kajian Ornamen Batu Silindrik Kumun Mudik Kota Sungai Penuh - Yogzan Putra Ilham; Yulimarni (VisArt: Jurnal Seni Rupa dan Design, 2025)
The study entitled "Kumun Mudik Cylindrical Stone, Kumun Debai District, Sungai Penuh City" aims to determine the existence, shape and type of ornaments on the Kumun Mudik cylindrical stone. The study uses a qualitative method with data collection techniques in the field through observation, interviews, documentation, and literature studies. Using research tools such as cameras, books, and pens. The research data analysis technique is through data grouping, analyzing data, drawing conclusions about the ornaments on the Kumun Mudik cylindrical stone. Writing conclusions as the findings in this study. The results of the study show that the Kumun Mudik cylindrical stone is a stone that has a distinctive ornament, namely in the form of human figure ornaments; straddled humans, geometric ornaments; large circles, small circles, expanding curves and Gothic curves. The shape of the ornament on the cylindrical stone is a single pattern, repeating pattern, asymmetrical and symmetrical patterns can be seen from the composition of the shape and size. Ornaments are applied to the front, top, right and left of the Kumun Mudik cylindrical stone.